Evaluation of knowledge and plaque scores in school children before and after health education - Mamata Hebbal; Anil V Ankola; Deepti Vadavi; Kunal Patel (Wolters Kluwer Medknow Publications, 2011)
Background: Health education is a process of transmission of knowledge and skills necessary for improvement in quality of life. The purpose of the present study was to evaluate the oral hygiene related knowledge and plaque scores of 12-year-old school children in Belgaum city before and after health education. Methods: Three schools of Belgaum city were randomly selected and assigned into one of three health educational groups - group I (audiovisual aids), group II (chalk and blackboard) and group III (no health education). Oral health related knowledge and plaque scores were assessed in all the groups before and after health education. Results: The mean knowledge score before intervention in group I was 7.94, in group II was 7.86 and in group III was 7.74 (P=0.86). After intervention, the mean knowledge score was 14.42 in group I, 12.7 in group II and 9.58 in group III (P<0.001). Plaque scores in the three groups were similar and statistically nonsignificant at baseline. After the oral health education, the mean plaque scores were 0.627 in group I, 0.8826 in group II and 1.0156 in group III. Within the group comparisons revealed a statistically improved oral hygiene with decreased plaque scores in all the three groups. Conclusion: Health education by audiovisual aids could be an effective preventive measure against plaque-related oral diseases.